2018
DOI: 10.4103/ccd.ccd_23_18
|View full text |Cite|
|
Sign up to set email alerts
|

Bulk-Fill restorative materials in primary tooth: An intrapulpal temperature changes study

Abstract: Objectives:It was aimed to investigate the temperature changes in primary teeth pulp chamber during the curing/setting of bulk-fill restorative materials with different nanoparticle contents.Methods:Twenty-five extracted, primary mandibular second molars were prepared as a Class II cavity. Five bulk-fill restorative materials consisting of Equia Fil (HVGIC), glass carbomer (GC) cement, Sonic Fill (SF), X-tra Fil (XF), and Quix Fil (QF) were tested. The measurement of the pulp chamber temperature changes (start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
5
13
0
Order By: Relevance
“…The obtained results for temperature changes associated with light-curing of the Filtek Bulk Fill Posterior are in accordance with previous studies reporting on other bulk-fill composites and cavity designs [29][30][31]. Bulk-fill composites, when tested in a water bath at 36-37 °C showed temperature increases in the pulp chamber ranging from 2.8 °C in primary [29] to 5 °C in permanent molars [31]. A flowable bulk-fill composite in deep cavities with the 0.5 mm remaining dentin thickness without a liner resulted in temperature changes up to 40 °C at the pulp dentin even though the material itself showed temperatures exceeding 50 °C at the bottom of the restoration [30].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The obtained results for temperature changes associated with light-curing of the Filtek Bulk Fill Posterior are in accordance with previous studies reporting on other bulk-fill composites and cavity designs [29][30][31]. Bulk-fill composites, when tested in a water bath at 36-37 °C showed temperature increases in the pulp chamber ranging from 2.8 °C in primary [29] to 5 °C in permanent molars [31]. A flowable bulk-fill composite in deep cavities with the 0.5 mm remaining dentin thickness without a liner resulted in temperature changes up to 40 °C at the pulp dentin even though the material itself showed temperatures exceeding 50 °C at the bottom of the restoration [30].…”
Section: Discussionsupporting
confidence: 91%
“…The obtained results for temperature changes associated with light-curing of the Filtek Bulk Fill Posterior are in accordance with previous studies reporting on other bulk-fill composites and cavity designs [29][30][31]. Bulk-fill composites, when tested in a water bath at 36-37 °C showed temperature increases in the pulp chamber ranging from 2.8 °C in primary [29] to 5 °C in permanent molars [31].…”
Section: Discussionsupporting
confidence: 90%
“…High-viscosity bulk-fill composites 2 of 10 (such as QuixFil, Dentsply, Konstanz, Germany) can be used to fill cavities entirely with only one material up to the occlusal surface, whereas low-viscosity bulk-fill composites (such as SureFil SDR flow, SDR, Dentsply) equate a final capping layer by a regular hybrid composite material because of inferior mechanical properties towing to their reduced filler load and filler composition [7,8]. It was shown that bulk-fill RBCs had the lowest shrinkage stress and shrinkage-rate values in comparison to regular flowable and non-flowable nanohybrid and microhybrid methacrylate-based RBCs and a silorane-based microhybrid RBC and do not increase the intrapulpal temperature in primary teeth during the curing/setting [9][10][11][12]. They were also able to reduce cuspal deflection in standardized Class II cavities compared with a conventional RBC (GrandioSO, VOCO, Cuxhaven, Germany) restored in an oblique incremental filling technique [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Resin based composites are universally used for all types of cavities in anterior and posterior teeth. They are considered to be the main option of countless dentists in direct restoration of carious lesions, because of their advantages as high strength, low thermal conductivity, modulus elasticity, hardness [1,2]. However, the drawbacks of this material are well known among the practitioners.…”
mentioning
confidence: 99%
“…In literature microleakage is defined as the clinically undetectable passage of bacteria, fluids, molecules or ions between a cavity wall and the restorative material [4][5][6][7]. Therefore the bulk-fill composites have been developed, in order to minimize the time of work required by the incremental techniques and decrease micro-leakage [2,4].…”
mentioning
confidence: 99%